VISIONARY PASTORAL LEADERSHIP AS A DRIVING FACTOR FOR CHURCH GROWTH: Empirical Evidence from Gereja Kristen Sangkakala Indonesia Jemaat Siloam - Yaterorogo Zebua; Hariyanto Hariyanto; Satria Omega Kadun; Beanto Benny (QUAERENS: Journal of Theology and Christianity Studies, 2026)
Leadership is a reflection of how a leader directs, convinces, organizes, and empowers the people he leads to understand and have a shared vision and mission. In the context of the church, a pastor is required to have a clear vision, because without a vision, ministry growth will not be achieved in real terms. This study aims to explore how the implementation of a pastor's visionary leadership affects the growth of the congregation at the Indonesian Sangkakala Christian Church (GKSI) Siloam Congregation. A visionary pastor is understood as a leader who is able to capture divine vision, inspire the congregation, make decisions based on values and wisdom, and be adaptive to the dynamics of the times. This study uses a quantitative approach through a survey method of 52 congregation respondents. The results of the study show that all indicators of visionary leadership have a significant and high correlation with church growth, both quantitatively and qualitatively. The highest correlation was found in decision making based on values and wisdom (r = 0.793), followed by inspiring and motivating the congregation (r = 0.700), having a clear vision from God (r = 0.679), and adaptive and responsive to changing times (r = 0.660). The overall correlation between visionary pastoral leadership and church growth was r = 0.769, indicating a very strong positive relationship. This finding confirms the importance of the character of visionary leadership in building a healthy, growing, and impactful church. This study also provides a practical contribution to local churches in developing leadership patterns that are in line with God's will and relevant to the needs of the times.